الاختام الاسطوانية في بلاد الرافدين من 2800 ق.م الى 539 ق.م - حماتي خليفة; عبد الحق بن يوسف (جامعة الوادي - University of Eloued, 2025)
تمثل الأختام الأسطوانية أهمية كبيرة باعتبارها من أهم المخلفات المادية الفنية، التي تساهم في التأريخ لحضارة بلاد الرافدين؛ فهي من أهم المصادر الأثرية لدراسة تاريخ هذه الحضارة، والتي يمكن تتبُّع نشأتها وتطورها وانتشارها عبر المراحل التاريخية المتعاقبة، وانتشارها حتى في معظم مناطق الشرق القديم. وقد اختُرعت هذه الأختام مع تطور الحياة في نهاية الألف الرابع ق.م. في عهد الوركاء، وارتبطت ارتباطاً وثيقاً بالتطور الاقتصادي الذي حدث خلال هذا العصر، ومثَّلت الدليل الحقيقي في معرفة الحقب التاريخية لبلاد الرافدين. وكان استعمل الختم يهدف منذ بداية اختراعه إلى التعبير عن ملكية الشيء المختوم، ويعبّر عن هوية صاحبه، ويحمل الصفة القانونية الملزمة أمام الحاكم. وقد تميزت الأختام بتعدد مواضيعها وتنوّع قيمها التي تعبِّر عن التحولات الفكرية والتطورات الثقافية التي مرت بها حضارة بلاد الرافدين عبر تاريخها الطويل. Cylinder seals represent great importance as one of the most important artistic material remnants, which contribute to the historiography of the Mesopotamian civilization. They are one of the most important archaeological sources for studying the history of this civilization, which can be traced in its origin, development and spread through successive historical stages, and spread even in most regions of the Ancient East. These seals were invented with the development of life at the end of the fourth millennium BC. It was closely associated with the economic development that took place during this era, and represented the real evidence in the knowledge of the historical epochs of Mesopotamia. From the very beginning of its invention, the use of a seal was intended to express the ownership of the sealed object, express the identity of its owner and carry the legally binding status before the courts. The seals were distinguished by the multiplicity of their themes and the diversity of their values, which express the intellectual transformations and cultural developments that the civilization of Mesopotamia has undergone throughout its long history.
مذكرة ماستر قسم التاريخ تخصص تاريخ الحضارات القديمة
Keywords: اختام الاسطوانية; بلاد الرافدين; Mesopotamia; Cylinder Seals